2019
DOI: 10.1097/j.pain.0000000000001750
|View full text |Cite
|
Sign up to set email alerts
|

A functional polymorphism in the ATP-Binding Cassette B1 transporter predicts pharmacologic response to combination of nortriptyline and morphine in neuropathic pain patients

Abstract: Many genetic markers have been associated with variations in treatment response to analgesics, but none have been assessed in the context of combination therapies. In this study, the treatment effects of nortriptyline and morphine were tested for an association with genetic markers relevant to pain pathways. Treatment effects were determined for single and combination therapies. A total of 24 functional single nucleotide polymorphisms were tested within the gene loci of mu-opioid receptor (OPRM1) gene locus, A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 87 publications
0
13
0
Order By: Relevance
“…They replicated this association in thirty-seven patients who were taking amitriptyline or nortriptyline along with morphine or fentanyl from the UK Biobank cohort (p=0.02). [5] Pharmacogenomics research in neuropathic pain are still at an early stage and this finding, like others, warrants replication in a large-scale cohort of patients with neuropathic pain. GWAS using large cohorts are also needed to uncover genetic variants associated with treatment response.…”
Section: Genetic Factorsmentioning
confidence: 80%
“…They replicated this association in thirty-seven patients who were taking amitriptyline or nortriptyline along with morphine or fentanyl from the UK Biobank cohort (p=0.02). [5] Pharmacogenomics research in neuropathic pain are still at an early stage and this finding, like others, warrants replication in a large-scale cohort of patients with neuropathic pain. GWAS using large cohorts are also needed to uncover genetic variants associated with treatment response.…”
Section: Genetic Factorsmentioning
confidence: 80%
“…Efficacy. Benavides et al [98] examined the association between genetic markers and the analgesic effect of the combination therapy with morphine and nortriptyline or the respective monotherapies in patients with neuropathic pain. Thirty-four SNPs in genes such as OPRM1, COMT, HT2RA, CYP2C19, and CYP2D6 were tested among the 25 neuropathic pain patients.…”
Section: Nortriptylinementioning
confidence: 99%
“…Even among individuals with seemingly singular neuropathic conditions (e.g., PHN), substantial diversity exists with respect to various clinical manifestations, sensory examination features, and presumably underlying pain mechanisms [21,22]. For instance, recently, Benavides et al found a functional polymorphism that could predict pharmacologic response to a combination of nortriptyline and morphine in NP patients [88].…”
Section: Implications For Researchmentioning
confidence: 99%